Pengaruh Jfaktor lingkungan terhadap intensitas pembungaan Melaleuca alternifolia - Liliana Baskorowati (Jurnal Pemuliaan Tanaman Hutan, 2013)
A detiled knowledge of a species flowering phenology is essential for estimating the reproductive success. Time, frequency and intencity of flowering may vary within species due to genetic differences also modified by abiotic and biotic factors. For M. alternifolia, knowledge of flowering phenology is important to develope an efficient breeding strategy. therefore, this study were undertaken to find out the environmental factors influenced the flowering intensity of M. alternifolia. Flowering phenology assessments were undertaken by counting the number of buds, inflorescences and capsules of individual trees at natural population for 6 years. Where as the assesment of all individual trees at seed orchards were carried out by estimating the number of buds, inflorecences  capsules using 8 point scales during 4 years. the average of maximum and minimum temperatures and the rainfall datas were collected from meteorogical station close to study sites. This study revealed that M. alternifolia was remarkably consistent in its main flowering period both within an outside of its natural range in new south wales. This suggest that floral initiation was associated with day length pattern between sites in this study. Flowering intensity  of M. alternifolia appears to be strongly associated with the total rainfall during the spring flowering season with low temperature as trigger of floral initiation during winter months.